(untitled) - Dr. Mahrukh Shakir; Farooq Shah; Uzair Ali (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
This research paper explores the tendencies of decolonization as exhibited by the characters in the novel, Twilight in Delhi, written by Ahmed Ali. This paper also highlights how the colonizers influenced the culture and social values of the colonized people in different ways in order to serve their own interests, without its harmful implications realized by the colonized ones. Through such an analysis and by using the theory of Orientalism by Edward Said, this study makes an attempt to bring awareness regarding decolonization and the related issues. The study find out that Mir Nihal thwarts any attempt made by his famil, particulary his son, Asghar to imitate and follow the Britiah lifestyle and culture.